STUDI PENENTUAN KOMPOSISI OPTIMUM CAMPURAN BAHAN BAKAR BIODIESEL–PETRODIESEL - Wirawan dkk, Soni S. (BPPT)
Biodiesel is a viable substitute for petroleum-based diesel fuel. Its advantages are improved lubricity, higher cetane number and cleaner emission. Biodiesel and its blends with petroleum-based diesel fuel can be used in diesel engines without any signifi cant modifi cations to the engines. Data from the numerous research reports and test programs showed that as the percent of biodiesel in blends increases, emission of hydrocarbons (HC), carbon monoxide (CO), and particulate matter (PM) all decrease, but the amount of oxides of nitrogen (NOx) and fuel consumption is tend to increase. The most signifi cant hurdle for broader commercialization of biodiesel is its cost. In current fuel price policy in Indonesia (especially fuel for transportation), the higher percent of biodiesel in blend will increase the price of blends fuel. The objective of this study is to assess the optimum blends of biodiesel with petroleum-based diesel fuel from the technically and economically consideration. The study result recommends that 20% biodiesel blend with 80% petroleum-based diesel fuel (B20) is the optimum blend for unmodifi ed diesel engine uses.Keywords: biodiesel, emission, optimum, blend